Nickel removal from electroplating industry wastewater: A bamboo activated carbon - D. Sivakumar; J. Nouri; T.M. Modhini; K. Deepalakshmi (Global Journal of Environmental Science and Management)
Water is prime requirement for surviving of any living beings.  The existence of surface water and groundwater sources are used for domestic, agriculture and industrial purposes in all over the world. Fresh water from both the water sources is highly contaminated in recent years because of rapid population growth, modern agriculture and industrial growth. Among them, contamination of water sources due to industrialization is high and it requires more attention to protect those water sources.  In this study, nickel removal from electroplating industry wastewater was done with the help of bamboo activated carbon.  The nickel removal from electroplating industry wastewater by bamboo activated carbon was done in this study at various adsorbent dosages (0.5, 1.0, 1.5 and 2.0 g/L), agitation speeds (25, 50, 75 and 100 rpm), particle sizes (2.36, 1.18, 0.6 and 0.3 mm), and concentration dilutions (0, 25, 50, 75 and 100%). The maximum removal percentage of nickel from electroplating industry wastewater using bamboo activated carbon was found to be 98.7 % at an optimum adsorption dosage 1.5 g/L, agitation speed 25 rpm, particle size 0.6 mm and concentration dilution 75 % with 110 min. contact time and 5.5 pH.  Functional groups available in a bamboo activated carbon before and after treatment were determined by fourier-transform infrared spectroscopy analysis. Fourier-transform infrared spectroscopy analysis specified that alkanes, carboxylic acids, esters, amides, amines, aromatic compounds, alkyl halides, ethers, alcohols, carboxylic acids, aldehydes functional groups in bamboo activated carbon was contributed for removing nickel from the electroplating industry wastewater. Isotherm models were used to know the adsorption behaviour of bamboo activated carbon for removing nickel from electroplating industry wastewater.  Isotherm results revealed that Langmuir model was best suited with the equilibrium data than Freundlich model.  Finally, this study concluded that bamboo activated carbon was best suited for removing nickel from electroplating industry wastewater.